2021
DOI: 10.1596/1813-9450-9682
|View full text |Cite
|
Sign up to set email alerts
|

The Scarring and Hysteresis Effects of Steep Recessions and the Implications for Fiscal Policy in ECA Transition Emdes

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The Keynesian Tourism destination competitiveness in Kenya effect as well as the scarring and hysteresis effects of public debt has shown that fiscal policies are key towards mitigating the effects of unemployment due to financial crises (Dombi and Dedak, 2019). The World Bank reports on the scarring and hysteresis effects of steep recessions have shown that fiscal policies during the great recession caused by the COVID-19 pandemic and subsequent impacts on 65 middle income countries has had a significant impact on productivity losses (World Bank, 2021). Several studies have evidenced the positive effects of fiscal policy on the level and rate of endogenous economic growth (Easterly and Robelo, 1993;Kopits and Symansky, 1998).…”
Section: Literature Review and Theoretical Implicationsmentioning
confidence: 99%
“…The Keynesian Tourism destination competitiveness in Kenya effect as well as the scarring and hysteresis effects of public debt has shown that fiscal policies are key towards mitigating the effects of unemployment due to financial crises (Dombi and Dedak, 2019). The World Bank reports on the scarring and hysteresis effects of steep recessions have shown that fiscal policies during the great recession caused by the COVID-19 pandemic and subsequent impacts on 65 middle income countries has had a significant impact on productivity losses (World Bank, 2021). Several studies have evidenced the positive effects of fiscal policy on the level and rate of endogenous economic growth (Easterly and Robelo, 1993;Kopits and Symansky, 1998).…”
Section: Literature Review and Theoretical Implicationsmentioning
confidence: 99%
“…The interconnectedness of markets suggests that hysteresis or scarring in the labour market can spill over to hysteresis in output and productivity (Arulampalam et al, 2001;Bell et al, 2020;Brownbridge & Canagarajah, 2021). Yet even without any spillover effects, as mentioned above by Cerra et al (2021), the second channel through which economic hysteresis can manifest itself is through a reduction in production and economic growth, halt of investments in general, and particularly in R&D, as companies may delay or reduce spending on R&D (Irons, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The interconnectedness of markets suggests that hysteresis or scarring in the labour market can spill over to hysteresis in output and productivity (Arulampalam et al, 2001;Bell et al, 2020;Brownbridge & Canagarajah, 2021). Yet even without any spillover effects, as mentioned above by Cerra et al (2021), the second channel through which economic hysteresis can manifest itself is through a reduction in production and economic growth, halt of investments in general, and particularly in R&D, as companies may delay or reduce spending on R&D (Irons, 2009).…”
Section: Introductionmentioning
confidence: 99%